2015
DOI: 10.4178/epih/e2015050
|View full text |Cite
|
Sign up to set email alerts
|

Tularemia and plague survey in rodents in an earthquake zone in southeastern Iran

Abstract: OBJECTIVES:Earthquakes are one the most common natural disasters that lead to increased mortality and morbidity from transmissible diseases, partially because the rodents displaced by an earthquake can lead to an increased rate of disease transmission. The aim of this study was to evaluate the prevalence of plague and tularemia in rodents in the earthquake zones in southeastern Iran.METHODS:In April 2013, a research team was dispatched to explore the possible presence of diseases in rodents displaced by a rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…Over the years, additional serology findings have verified that tularemia exists also in other parts of Iran. Recent studies of rodents in the southeast and west of Iran showed the presence of antibodies against F. tularensis (Pourhossein et al, 2015 ; Mostafavi et al, 2017 ). In another study of humans in 2014 in the Sistan and Baluchistan province southeast of Iran, the seroprevalence of tularemia among butchers and workers of slaughterhouses was estimated to be 6.5% (Esmaeili et al, 2014b ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the years, additional serology findings have verified that tularemia exists also in other parts of Iran. Recent studies of rodents in the southeast and west of Iran showed the presence of antibodies against F. tularensis (Pourhossein et al, 2015 ; Mostafavi et al, 2017 ). In another study of humans in 2014 in the Sistan and Baluchistan province southeast of Iran, the seroprevalence of tularemia among butchers and workers of slaughterhouses was estimated to be 6.5% (Esmaeili et al, 2014b ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of these studies suggest that tularemia may be underdiagnosed in Iran and that enhanced disease surveillance would be valuable (Esmaeili et al, 2014a , b ; Khoshdel et al, 2014 ; Zargar et al, 2015 ). In 2013, F. tularensis -specific antibodies were found in rodents in the southeast and west of Iran indicating that small mammals may be involved in disease transmission (Pourhossein et al, 2015 ; Mostafavi et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The first human case of tularemia was reported in 1980 in Marivan city in Kurdistan province (6) and recently the second case of tularemia were reported in 2017 from a village near Marivan city (7). In recent years, the antibody against tularemia was also reported in rodents in the southeast and west of Iran (8, 9). In a study in 2014 in Sistan and Baluchistan province, southeast of Iran, the seroprevalence of tularemia amongst butchers and slaughterhouse workers was 6.52% and in another study on high risk groups in Kurdistan province, west of Iran, prevalence of antibodies against tularemia was reported 14.4% (10, 11).…”
Section: Introductionmentioning
confidence: 92%
“…Due to the fact that tularemia is an endemic disease in Turkey (Iran's northwest neighbor) and several clinical cases of this disease are reported annually from that country (18), and because of the recent detection of tularemia antibodies in the human population of the Republic of Azerbaijan (Iran's northern neighbor) (15), and recent evidences of the circulation of the bacteria in Iran (811), taking into account the fact that there is no information respect to contamination of water samples to Francisella spp. in Iran, this study was conducted to evaluate the surface waters in two north western provinces, Kurdistan and West Azerbaijan.…”
Section: Introductionmentioning
confidence: 99%
“…In a study in 1973, tularemia was reported in a hedgehog in southeastern Iran [17,18]. Recently, tularemia infection was detected in high-risk human populations and rodents of Sistan and Baluchistan province, Southeast of Iran [19,20].…”
Section: Introductionmentioning
confidence: 99%